Acne: morphologic and vascular study of lesions and surrounding skin by means of optical coherence tomography. (19th July 2017) - Manfredini, M.; Greco, M.; Farnetani, F.; Ciardo, S.; De Carvalho, N.; Mandel, V.D.; Starace, M.; Pellacani, G.
Abstract: Background: Acne vulgaris is a disease of the pilosebaceous unit, characterized by hyper‐keratinization process, comedos formation and inflammatory reactions. Objective: The definition of the morphology and the vascularization of acne lesions by means of dynamic optical coherence tomography (D‐OCT), to non‐invasively define the alterations occurring during the acne development and patient therapeutic management. Methods: A set of standardized clinical pictures and D‐OCT images were acquired from 114 acne lesions of 31 volunteers, presenting mild to moderate acne and evaluated by experts. Fifteen patients treated with oral antibiotics were followed during time at 0, 20, 40, and 60 days. Results: Optical coherence tomography enabled to identify vascular and morphological aspects characterizing different types of acne lesions. Oral antibiotic treatment improved the morphologic features and decreased the digitally reconstructed vascular signal during time. Conclusion: The characterization of acne lesions and the identification of vascular pattern in acne lesions through D‐OCT, corresponding to blood vessel dilation and inflammatory associated hyper‐vascularization, may have important clinical consequences in the assessment of acne severity, therapeutic decisions and treatment efficacy monitoring.